Effects of some herbs and spices on hypercholesterolemic rats - Soltan, S. S. A.; Abdel-Wabab, H. M. F. (2006)
The aim of this study, is to assess the effects oftunneric powder. mustard seed powder, marj oram leaf, rosemary powder, ginger powder and red pepper powder as hypocholesterolemic, hypolipidemic and antioxidant agents in hypercholesterolemic rats, Forty eight male albino rats were divided into 8 groups: First group was fed on normal basal diet (negative control group), Group 2 hypercholesterolemic hyperlipidemic group fed on high cholesterol-high fat diet and from group 3 to group 8 fed on high cholesterol-high fat diet and supplemented by the following: turmeric (group 3), mustard (group 4). marjoram (group 5), rosemary (group 6), ginger (group 7) and red pepper (group 8), The biological effects of these herbs and spices were investigated by food intake, final body weight, serum lipid profiles and liver cholesterol, triacylglycerol and liver glutathione. There was significant increase in each of serum total cholesterol, triacylglycerol, very low denisty lipoprotein (VLOL) and low denisty lipoprotein (LOL) cholesterol, total liver cholesterol and triacylglycerol and also liver glutathione in hypercholesterolemic group when compared to control group.
Includes references.
Summary in Arabic.
1
Keywords: Cholesterol -- Research; Herbs -- Therapeutic use -- Research; Herbs -- Utilization